الاختيار والتوافق الزواجي وعلاقته بالنظرة الشرعية في المجتمع السعودي: دراسة مسحية على عينة من منطقة مكة المكرمة بالمملكة العربية السعودية - الزهراني، نايف بن أحمد بن جمعان الجمعان (جامعة الأزهر - كلية التربية, 2020)
تناولت الدراسة تطبيق النظرة الشرعية في المجتمع السعودي ممثلا في منطقة مكة المكرمة ومحافظتها، واستخدمت الدراسة المنهج الوصفي، وقد تم توزيع استبانة تمت الإجابة عليها من قبل 120 شخصا من مدن مكة المكرمة وجدة والطائف، بحثا عن إجابة لمجموعة من التساؤلات الرئيسية والتي كانت تهدف لقياس أثر تطبيق النظرة الشرعية على الاختيار والتوافق الزواجي، وقد أكد ما نستهم تصل إلى 83% بأن النظرة الشرعية تساعد في إيجاد التوافق الزواجي المأمول، كما وافق ما يقارب الـ 92% على أن النظرة الشرعية عامل مهم من عوامل اختيار الشريك المناسب، كما بينت الدراسة أخيراً على أن المجتمع مرتبط ارتباطاً وثيقا بالأسس الدينية التي تعلمها ومن بعدها العادات والتقاليد كمنهج رئيسي في تطبيق النظرة الشرعية، وقد خلص البحث لتوصيات كان من أهمها إعطاء الحق الكامل للخاطب والمخطوبة في ممارسة حقهما بتطبيق النظرة الشرعية إضافة إلى التأكيد عليهما بضرورة النقاش الإيجابي أثناء النظرة الشرعية والمساعد على الاختيار والتوافق الزواجي المأمول.
This research was conducted on the implementation of the legitimate view in the Saudi society represented in the region of Makkah and cities which belong to it. The distributed questionnaire was answered by 120 people from the cities of Makkah ‘ Jeddah and Taif, seeking an answer to number of key questions which were aimed to measuring the impact of the legitimate view on Choice and marital compatibility. 83% of the respondents confirmed that the legal view helps to find the desired marital compatibility ‘ and nearly 92% agreed that the legal view is an important factor in choosing the right partner. Finally the study showed that the society is closely linked to the religious foundations that it has learned and then the customs and traditions as a major approach in the application of the religious view. The study concluded the recommendations of the most important of which give the full right to the marriage parties in the exercise of their right to apply the view of legitimacy in addition to the emphasis on the need for positive debate during the view of legitimacy which help on choice and hoped marital harmony.
Keywords: التوافق الزواجي -- المجتمع السعودي -- البرامج الوقائية -- الحياة الزوجية -- النظرة الشرعية